The Role of Profitability and Liquidity in Mitigating Financial Distress Risk - Nico Adikusuma; Novita Febriany (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study examines the role of profitability and liquidity in mitigating financial distress risk. The sample consists of 26 State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period, selected through purposive sampling. Multiple linear regression analysis was employed to analyze the relationship between profitability, liquidity, and financial distress risk. The results indicate that the unique characteristics of SOEs, such as their strategic role in public service and national development, as well as government support in the form of state capital participation (PMN), debt restructuring, and other special policies, cause SOEs not to rely entirely on financial performance to maintain business continuity. In addition, accounting policies, government regulations, and political interests also influence the financial condition of SOEs, so financial ratios do not always reflect the actual distress condition. These findings suggest that SOEs have distinct characteristics that differ from private companies. Therefore, financial distress analysis in SOEs should consider not only financial indicators but also institutional, regulatory, and government support factors.